2020
DOI: 10.1108/ijlss-07-2019-0074
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of lean in health care environments: an update of systematic reviews

Abstract: Purpose Even though the implementation of lean in health care environments is relatively recent, it has been receiving a lot of attention in recent years. Partly because of the fact that it is a recent field of practise and research and partly because the number of works developed in this field has grown rapidly, it is important to frequently update the perspectives on this field of investigation. Thus, this study aims to review the implementation of lean tools and techniques applied to hospital organizational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
2
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 133 publications
0
46
2
4
Order By: Relevance
“…The intention of using the Lean approach on all organization sectors emerged on the 1990s with the term "Lean enterprise" (LE), and this concept encompasses the use of Lean approaches from the manufacturing sector to the whole organization, including service processes (Womack & Jones, 1994, p. 93). Womack & Jones (1994) Lean philosophy can provide vast benefits when implemented holistically and instructed as a mutually beneficial strategy (Hallam & Contreras, 2018;Waring & Bishop, 2010); however, such approaches are missing in hospital operations management (Lima et al, 2020). Anyhow, the waste reduction approach can be applied independently in order to make progress in terms of organizational culture with the aim of implementing the Lean philosophy or even with the intention of maximizing the use of available resources.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…The intention of using the Lean approach on all organization sectors emerged on the 1990s with the term "Lean enterprise" (LE), and this concept encompasses the use of Lean approaches from the manufacturing sector to the whole organization, including service processes (Womack & Jones, 1994, p. 93). Womack & Jones (1994) Lean philosophy can provide vast benefits when implemented holistically and instructed as a mutually beneficial strategy (Hallam & Contreras, 2018;Waring & Bishop, 2010); however, such approaches are missing in hospital operations management (Lima et al, 2020). Anyhow, the waste reduction approach can be applied independently in order to make progress in terms of organizational culture with the aim of implementing the Lean philosophy or even with the intention of maximizing the use of available resources.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…These and other authors [ 10 , 20 , 22 ], have also indicated that the application of each tool depends on the real situation in which the organization or company finds itself, as experts in the field do not agree when it comes to identifying them, classifying them, and proposing their scope of application. These tools can be used independently or in conjunction with other tools (e.g., process diagram, Ishikawa diagram, spaghetti diagram) not necessarily related to production process improvement in themselves, but that are equally useful for the development of the Lean philosophy and that serve the continuous improvement of the organization.…”
Section: Introductionmentioning
confidence: 99%
“…Both labour law codes, as well as the potential conflict between management and workers, may make it impossible to adopt lean government policies [8]. Nevertheless, the health sector has been demonstrating a great capacity to adapt to the principles of the philosophy originated in Toyota in what can called lean healthcare, which is a very recent concept [9]. To advocate a management policy based on lean healthcare concepts means a constant search to provide improved patient services using a lower number of resources.…”
Section: Introductionmentioning
confidence: 99%
“…The exact beginning of the application of the lean healthcare concept is somewhat diffuse, however pioneering work stands out [11], where the author transports productive technology to the hospital context in order to reduce inventories. Since then, multiple publications have appeared in the scientific community [9], addressing several applications of different Lean tools in healthcare services, such as the application of SMED techniques to reduce the setup time of an operating room [12], the application of performance indicators such as the overall equipment effectiveness of operating rooms [13], or the application of the methodology 5S in a hospital establishment [14]. Research in lean healthcare has been growing almost exponentially; however, according to Proudlove et at.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation